Determining of the Variety of Genotypes in Salmonella Typhimurium by ERIC-PCR - R Ranjbar (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2013)
BACKGROUND AND OBJECTIVE: Salmonella enterica serovar Typhimurium is one of the most prevalent Salmonella serovars worldwide. Molecular typing of Salmonella serovars is of epidemiologic importance. The current research was carried out to study the genetic diversity of Salmonella typhimurium by enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR).METHODS: In a cross-sectional descriptive study that was carried out from 2007 to 2009, clinical samples including stool and blood were collected from the patients admitted to three hospitals in Tehran, Iran. All Salmonella stains were cultured and diagnosed by standard microbiological methods. Serotyping was carried out by commercially available antisera and the genetic diversity between the strains was determined by ERIC-PCR.FINDINGS: Among 650 clinical samples, twenty one salmonella typhimurium were identified. ERIC-PCR differentiated Salmonella typhimurium strains into nine genetic clusters (T1-T9). Thirty three percent of the strains were clustered into T1 (7 isolates) followed by T2 (6 strains, 29%), T3 (2 strains, 10%) and T4-T9 (each one strain). CONCLUSION: The results showed that endemic Salmonella typhimurium strains isolated in Tehran could be attributed to divers ERIC clusters and ERIC-PCR has been evaluated as a good approach for molecular typing of Salmonella typhimurium strains.